Stem cell and progenitor fate in the mammalian intestine: Notch and lateral inhibition in homeostasis and disease. (8th April 2015) - Sancho, Rocio; Cremona, Catherine A; Behrens, Axel
Abstract The control of cell fate decisions is vital to build functional organs and maintain normal tissue homeostasis, and many pathways and processes cooperate to direct cells to an appropriate final identity. Because of its continuously renewing state and its carefully organised hierarchy, the mammalian intestine has become a powerful model to dissect these pathways in health and disease. One of the signalling pathways that is key to maintaining the balance between proliferation and differentiation in the intestinal epithelium is the Notch pathway, most famous for specifying distinct cell fates in adjacent cells via the evolutionarily conserved process of lateral inhibition. Here, we will review recent discoveries that advance our understanding of how cell fate in the mammalian intestine is decided by Notch and lateral inhibition, focusing on the molecular determinants that regulate protein turnover, transcriptional control and epigenetic regulation.